IHRM: A BLIBIOMETRIC ANALYSIS - Pramita, Cindy (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
The globalization of business has created a need for companies to develop effective international human resource management practices. IHRM is a critical area of research in the field of human resource management, as it encompasses issues related to the management of people in a global context. Given the complexity of managing human resources across national borders, it is important to understand the factors that influence IHRM practices and their impact on organizational outcomes. This research aims to investigate the interrelationships between IHRM and other related topics, such as global and domestic hiring practices. The data used consists of 100 articles indexed by Scopus for the period of 2018-2023. This research method employs bibliometric analysis using the VOSviewer software. The results of the analysis were visualized through co-authorship, co-occurrence, and co-citation, namely the most frequently identified article citations from the 10 highest citation groups. It shows that IHRM commitment is related to other issues such as cultural divergence, IHRM strategy, HRM practices convergence, expatriates, and global HR hiring. This review aims to serve as a reference for future research on IHRM strategy and other relevant variables.